Describing the Customers’ Perception of Unilever’s Dualithic Approach has had on its Sub-Brands’ Brand Equity - Twiddy, Jayd, Lynne (The IIE, 2017)
This was a small-scale qualitative research study, which analysed the impact an organisational strategy and structural shift has had on both the parent-brand and its subbrands’ brand image, brand loyalty and brand equity elements as perceived by consumers. Unilever is a world-wide Fast Moving Consumer Goods (FMCG) organisation that has recently shifted its strategy shift, from a silent parent-brand to an endorsed parent-brand. The aim of this study was to analyse the general consumer’s perception towards both parent-brand and sub-brand, in relation to Unilever’s brand strategy shift from a Mulitilithic Approach to a Dualithic Approach. While determining whether the shift has had a positive influence on both parent and sub brands; thus encouraging other Fast Moving Consumer Goods (FMCG) organisations, such as Pioneer Foods, Tiger Brands, etc. to implement and shift towards the same strategy. Information was gathered through 15 face-to-face interviews, and emails with general consumers within the greater Durban area. Due to the descriptive qualitative nature of the study, the samples were not generalised to the total population, but rather develop an indepth study of the main phenomenon. The insights provided by the study lead to meaningful key findings. It was clear that participants were aware of many parent-brands within the South African Market, however many were unable to identify the products of each parent-brand. The participants purchase particular FMCG products based on their perception of value (quality vs price), however these products can be seen as price dependent. It was also determined that products and/or brands that communicate elements of be environmentally friendly, transparent and accountable, this can impact the participants purchasing decisions. From the key findings, recommendations for Unilever and other FMCG organisations within the South African market were made.
Keywords: Brand Strategy; Consumer Behaviour; Fast Moving Consumer Goods (FMCGs); Branding; Brands